2010
DOI: 10.1029/2009ja014979
|View full text |Cite
|
Sign up to set email alerts
|

Space Technology 5 observations of the imbalance of regions 1 and 2 field‐aligned currents and its implication to the cross‐polar cap Pedersen currents

Abstract: [1] In this study, we use the in situ magnetic field observations from Space Technology 5 mission to quantify the imbalance of region 1 (R1) and region 2 (R2) currents. During the 3 month duration of the ST5 mission, geomagnetic conditions range from quiet to moderately active. We find that the R1 current intensity is consistently stronger than the R2 current intensity, both for the dawnside and the duskside large-scale field-aligned current system. The net currents flowing into (out of) the ionosphere in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…The correlation between the FACs and the solar wind pressure agrees with the work of Siscoe et al [] that region 1 currents play role in providing the current to balance the enhancement of the solar wind pressure at the magnetopause. The positive relationship between the FACs and K p index is consistent with the work of Le et al [], which indicates that these FACs at the Λ b are probably the convection type region 1 currents [ Nishida , ; Thomsen , ; Siscoe and Lu , ]. Frank and Gurnett [] found that the Λ b spatially coincides with the reversal of the convection electric field.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The correlation between the FACs and the solar wind pressure agrees with the work of Siscoe et al [] that region 1 currents play role in providing the current to balance the enhancement of the solar wind pressure at the magnetopause. The positive relationship between the FACs and K p index is consistent with the work of Le et al [], which indicates that these FACs at the Λ b are probably the convection type region 1 currents [ Nishida , ; Thomsen , ; Siscoe and Lu , ]. Frank and Gurnett [] found that the Λ b spatially coincides with the reversal of the convection electric field.…”
Section: Discussionsupporting
confidence: 85%
“…At the ionosphere latitude, both the case study [ Anderson et al , ; Siscoe and Lu , ] and the superposed epoch analysis [ Coxon et al , ] show that the region 1 currents are enhanced during substorm activities. Interplanetary magnetic field B z is also investigated (not shown here), which shows large data scatter but not a clear effect of the magnetosphere's half‐wave rectifier [ Le et al , ]. In this study, the statistics with Cluster data is limited by representing the whole current sheet with the one‐point observation so that it cannot take into account the local time distribution and current development [ Clausen et al , ; Coxon et al , ; Gjerloev et al , ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data for the four higher latitude orbits are in Figures 2a-2d, all of which are above the auroral zone at local noon. The magnetic field observations for these higher latitude orbits exhibit those of typical field-aligned current signatures [Le et al, 2009[Le et al, , 2010. In Figures 2a, 2b, and 2d, it is clear that the spacecraft crosses the auroral zone twice, and thus the magnetic field perturbations associated with large scale field-aligned currents are evident in both morning and afternoon side separating by polar cap magnetic field.…”
Section: Observation Overviewmentioning
confidence: 80%
“…In the case that closure currents generally occur between the peak FACs, larger separation would indicate closure currents over larger areas. This is likely the case at the dawn and dusk sectors where R1/R2 FACs commonly close between one another (Hruška, ) and imbalances largely close over the polar cap (Le et al, ). On the dayside the separation between peaks is smaller, potentially resulting in localized current closure.…”
Section: Resultsmentioning
confidence: 99%